Ammonia, ammonium, and the risk of asthma: A register-based case–control study in Danish children. Issue 3 (September 2018) - Holst, Gitte; Thygesen, Malene; Pedersen, Carsten B.; Peel, Robert G.; Brandt, Jørgen; Christensen, Jesper H.; Bønløkke, Jakob H.; Hertel, Ole; Sigsgaard, Torben
Abstract : Background: Evidence concerning the health effects of exposure to fine particulate matter less than 2.5 μm in diameter (PM2.5 ) and particulate components such as ammonium (NH4 + ) is limited. We aimed to investigate gaseous ammonia (NH3 ), particulate ammonium (NH4 + ), the total concentration of these pollutants (NHx ), and PM2.5 and their association with asthma in Danish preschool children. Methods: Estimates of incidence rate ratios associated with exposure to air pollution were calculated for children followed for the development of childhood asthma (n = 335, 629) from their first to their sixth birthday during the time period 2006–2012 using a time-matched case–control design by combining register information. Modeled average concentrations of NH3, NH4 +, NHx, and PM2.5 (5.56 km × 5.56 km grid resolution) during the past 3 months prior to the date of first diagnosis of asthma for cases. Results: We identified 12, 935 incident cases of asthma. The base adjusted hazard ratio of incident asthma was 1.74 for children exposed to the highest decile of NH3 exposure (95% confidence interval = 1.60, 1.89) compared to children exposed to the lowest decile of NH3 exposure during the past 3 months prior to first diagnosis. Similar hazard ratios were found for the highest levels of NH4 + (2.33; 2.04, 2.65) and NHx (1.82; 1.68, 1.96). The positive associations were slightly attenuated, when adjusting for socioeconomic status, but disappeared when additionally adjusting for region, except in a two-pollutant model including NH4 + and PM2.5 . No association was found with PM2.5 . The findings were robust when using different exposure time windows. Conclusions: Increased NH4 + exposure may be a risk factor for the onset of asthma in preschool children. Abstract : Supplemental Digital Content is available in the text.